32 The Impact of Haemoglobin Reduction on Short- and Long-Term Mortality Following Primary Percutaneous Coronary Intervention for St-Elevation Myocardial Infarction-analysis from a Real World Stemi Population. (31st May 2014) - Nazri, Shah Mohd; Constantine, Andrew; Jagathesan, Rohan; Kabir, Alamgir; Sayer, Jeremy; Robinson, Nicholas; Aggarwal, Rajesh; Tang, Kare; Kelly, Paul; Gamma, Reto; Clesham, Gerald; Davies, John; et al.
Abstract : Introduction: Mortality following ST-elevation myocardial infarction has declined significantly with the advent of primary PCI (PPCI). Concurrent use of antiplatelet agents has further decreased complication rates and mortality; however, these agents confer an increased bleeding risk, an independent risk factor for mortality. This retrospective study assesses the effect of blood loss on short- and long-term mortality and its association with clinical characteristics in a real world population of patients undergoing PPCI at a tertiary referral centre in the UK. Methods: All patients accepted for PPCI within the period of September 2009 to November 2011 were eligible for inclusion in the study. Patient data were obtained from our Cardiac Services Database System (Phillips CVIS) and mortality data were gathered from the Summary Care Record (SCR) database. Statistical comparisons of continuous variables were made by one-way ANOVA. Categorical variables were compared using the chi-squared test. A P value of < 0.05 was taken to indicate statistical significance. Results: 1403 patients with recorded admission and discharge haemoglobin levels were included in this analysis. Characteristics and clinical outcomes were compared in three groups according to the degree of haemoglobin reduction (Table 1 ). Patients with a reduction in haemoglobin were more likely to be female, slightly older and have prior history of MI. Patients with a significant reduction in haemoglobin were more likely to have received abciximab. Thirty-day mortality was significantly higher in the group with a haemoglobin drop (Table 1 ) as was overall mortality (hazard ratio 1.8, 95% CI 1.2–2.5) during a mean follow-up period of 2.1 years (Figure 1 ). Conclusions: Our retrospective analysis in a large cohort of patients confirms recent data suggesting an adverse association between a reduction in haemoglobin following PPCI and long-term mortality. Further work is required on strategies to reduce bleeding risk and hence improve clinical outcome following PPCI.